DINAMIKA INDEKS DEMOKRASI INDONESIA PADA PERIODE KEDUA PEMERINTAHAN JOKO WIDODO: ASPEK KEBEBASAN SIPIL DAN KELEMBAGAAN DEMOKRASI - Al Faizi, Moh.; ikmal, Moh.; Basri, Hasan (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Over the past five years, Indonesia's democracy index has experienced a significant decline. This indicates that the quality of democracy in Indonesia is on the verge of collapse. During President Joko Widodo's second term, the democracy index has continued to experience dynamics. Therefore, the purpose of this study is to measure the extent to which aspects of civil liberties and democratic institutions are operating in accordance with democratic principles. This research used qualitative methods with a descriptive-analytical approach. The results of this study explain that the quality of democracy in Indonesia is declining, starting with the disappearance of civil liberties and democratic institutions that have begun to be used as tools for political power. Consequently, the democratic system of government that has long been maintained and nurtured is moving towards electoral autocracy.